Contrasting Expression of Rhizobial Phytase in Nodules of Two Soybean Cultivars Grown Under Low Phosphorus Availability - Cerecetto, Victoria; Beyhaut, Elena; Amenc, Laurie; Trives, Carlos; Altier, Nora; Drevon, Jean-Jacques (Frontiers in Sustainable Food Systems, 2021)
Phosphorus deficiency can be a major limitation to legume growth when plant nitrogen nutrition depends on symbiotic nitrogen fixation. One possible approach to overcome this constraint is the selection of plant and rhizobial genotypes capable of metabolizing complex forms of phosphorus in the nodules. The aim of this research was to study the rhizobial phytase transcript abundance in nodules of two soybean cultivars (Glycine max (L.) Merr.) grown under two different phosphorus conditions in hydroaeroponic conditions. An in situ RT-PCR of a rhizobial phytase was performed in microtome sections of soybean nodules of two cultivars growing under phosphorus sufficiency vs phosphorus deficiency. The results showed that the plant cultivar may influence the level of transcript abundance of the bacterial phytase and in consequence affect the phosphorus use efficiency of nitrogen-dependent Bradyrhizobium spp.-soybean symbioses. Thus, the selection of a good combination of plant and rhizobial genotypes should be a priority when breeding for phosphorus deficiency is performed.